Impact of CAP on the Cash-Flow Components in Slovak Agriculture - Zuzana Čierna; Tomáš Rábek; Marián Tóth (Polityki Europejskie, Finanse i Marketing)
The primary goal of the paper is to state the development of cash-flow in Slovak agriculture. The observed period covers 11 years, which offers the opportunity to analyze three separate periods: the pre-accession period 2000-2003, the old CAP from 2004-2006 and the current CAP 2007-2010. The data for individual companies - corporations - were obtained from The Research Institute of Agricultural and Food Economics (RIAFE) for the period 2000 – 2010. The research has shown that entering EU and adopting Common agricultural policy had a positive impact on the cash flow from operating activities. We also did identify lower investments (CF from investing activities) since 2009. One of the reasons for that can be the impact of the financial and economic crisis. The impact on net cash flow was a higher volatility.